Source of magnetic field effects on the electrocatalytic reduction of CO2 - Player, T; Hore, P (AIP Publishing, 2020)
We present an analysis of reported magnetic field effects on the yield of formic acid produced by electrocatalytic reduction of carbon dioxide at a nanoparticle tin electrode (Pan et al., J. Phys. Chem. Lett. 11 (2020) 48–53). Radical pair spin dynamics simulations are used to show that: (1) the g mechanism favoured by Pan et al. is not sufficient to explain the observed magneto-current. (2) Field-dependent spin relaxation, resulting from the anisotropy of the g-tensor of CO2  , combined with the coherent singlet-triplet interconversion arising from isotropic hyperfine and Zeeman interactions, can quantitatively account for the observed magnetic field effect. (3) Modification of hyperfine interactions by isotopic substitution (1H  2H and/or 12C  13C) could be used to test both the proposed reaction mechanism and the interpretation presented here.